An Integration Of Emotional Maturity Human Resources Training Strategy To Improve Student Harmony Of Medan Aviation Polytechnic - Muhammad Caesar Akbar; Wawan Setyawan (Sean Institute, 2025)
This study discusses how emotional maturity can be integrated into human resource training and development strategies to enhance harmony among students at Medan Aviation Polytechnic. Students, who are generally aged between 18 and 23, are in the early stages of adulthood, which often face emotional instability. Therefore, it is important to manage oneself and channel emotions positively. This research method uses a descriptive quantitative research type to determine the effect of extracurricular activities, outbound, and leadership training on the emotional maturity of Medan Aviation Polytechnic students by using the interview method in its preparation. The population of this study was all students of Medan Aviation Polytechnic who had participated in the activities. The sample was taken using a purposive sampling technique with a total of 109 students.Through extracurricular activities and training programs, the Medan Aviation Polytechnic strives to cultivate emotional maturity that not only enhances harmony among students from diverse backgrounds but also prepares them to become professional workers. With a humanistic approach based on the principles of mutual respect, mutual learning, and mutual support, students are taught emotional skills that contribute to creating a harmonious campus environment.